PENERAPAN MODEL PEMBELAJARAN STORYTELLING BERBANTUAN MEDIA POP-UP BOOK UNTUK MENINGKATKAN KETERAMPILAN MENYIMAK CERITA RAKYAT SISWA SEKOLAH DASAR - Laila Qurratun Nada; Iis Aprinawati; Putri Hana Pebriana; Yenni Fitra Surya; Fadhilaturrahmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low listening skills of students in folklore lessons in Indonesian Language subject at grad VB of SDN 004 Salo. One solution to overcome this problem is by applying the Storytelling learning model assisted by Pop-Up Book media. The purpose of this study is to improve students’ listening skills in folklore learing in Indonesian Language subject. The research method used is Classroom Action Research (CAR), conducted in two cycles. Each cycle consisted of two meetings and four stages: planning, implementation, observation, and reflection. The research was carried out in August 2025. The subjects of this study were 14 fifth-grade students consisting of 8 boys dan 6 grils. Data collection techniques included observation, written tests, and documentation. Before the action was taken, the students’ listening skills in folklore were 29%. In cycle I meeting I, itu increased to 36%, and in cycle I metting II, it further increased to 43%. In cycle II meeting I, it rose to 57%, and in cycle II meeting II, it reached 86%. Thus, it can be concluded that the use of the Storytelling learning model assisted by Pop-Up Book media can improve students’ listening skills in folklore in the Indonesian Language subject at SDN 004 Salo.